2009
DOI: 10.1017/s1368980008004539
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and metabolic syndrome factors in a non-diabetic Italian population

Abstract: Objective: To examine the relationship between dietary patterns and metabolic syndrome. Design: Population-based cross-sectional study. The K-means clustering method was used to identify dietary patterns and logistic regression models were used to compare the adjusted prevalence rates of metabolic syndrome factors, stratifying by obesity status. Setting: The 1992-3 Italian Bollate Eye Study, a population-based survey carried out in the town of Bollate (Milan), Italy. Subjects: A total of 1052 non-diabetic Ital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Seven of these epidemiological studies had longitudinal ( 21 27 ) design and the remaining ( n 32) had a cross-sectional design. The studies were conducted in twenty-three different countries including Algeria ( 28 ) , Australia ( 29 ) , Bulgaria ( 28 ) , China ( 30 ) , Egypt ( 28 ) , Finland ( 31 ) , France ( 25 ) , Germany ( n 2) ( 32 , 33 ) , Greece ( n 4) ( 28 , 34 36 ) , Guatemala ( 37 ) , Iran ( n 3) ( 38 40 ) , Italy ( n 3) ( 28 , 41 , 42 ) , Japan ( 43 ) , Korea ( n 4) ( 44 47 ) , Lebanon ( 48 ) , Mexico ( 49 ) , Portugal ( 50 ) , Samoa ( 51 ) , Serbia-Montenegro ( 28 ) , Spain ( 52 ) , Sweden ( 53 ) , Taiwan ( 26 ) and the USA ( n 10) ( 3 , 21 24 , 54 58 ) . The studies enrolled from 323 ( 48 ) to over 93 209 ( 26 ) participants.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of these epidemiological studies had longitudinal ( 21 27 ) design and the remaining ( n 32) had a cross-sectional design. The studies were conducted in twenty-three different countries including Algeria ( 28 ) , Australia ( 29 ) , Bulgaria ( 28 ) , China ( 30 ) , Egypt ( 28 ) , Finland ( 31 ) , France ( 25 ) , Germany ( n 2) ( 32 , 33 ) , Greece ( n 4) ( 28 , 34 36 ) , Guatemala ( 37 ) , Iran ( n 3) ( 38 40 ) , Italy ( n 3) ( 28 , 41 , 42 ) , Japan ( 43 ) , Korea ( n 4) ( 44 47 ) , Lebanon ( 48 ) , Mexico ( 49 ) , Portugal ( 50 ) , Samoa ( 51 ) , Serbia-Montenegro ( 28 ) , Spain ( 52 ) , Sweden ( 53 ) , Taiwan ( 26 ) and the USA ( n 10) ( 3 , 21 24 , 54 58 ) . The studies enrolled from 323 ( 48 ) to over 93 209 ( 26 ) participants.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, cluster analysis has been used firstly to derive dietary patterns, and thereafter differences in (71) CS nutritional biomarkers explored in an attempt to examine the relationship between the two. It is hoped that this will enhance the knowledge base as to whether these dietary patterns are biologically meaningful.…”
Section: Dietary Patterns and Associations With Nutritional Biomarkersmentioning
confidence: 99%
“…Dietary patterns have also been explored in relation to the metabolic syndrome. In one study of Italian non-diabetic adults, the highest prevalence of the metabolic syndrome was found in the ‘starch’ and ‘animal products’ patterns and the lowest prevalence found in a ‘vegetable oil and fat spread’ pattern and a ‘vegetable and fruit’ pattern ( 71 ) . Furthermore, in a Swedish study, it was reported that in males the ‘many foods and drinks’ and the ‘white bread’ pattern and in females the ‘white bread’ pattern only had increased risks of metabolic risk factors ( 34 ) .…”
Section: Dietary Patterns and Associations With Chronic Diseasesmentioning
confidence: 99%
“…These fats are solid at room temperature and are mainly found in animal fats such as red meats and dairy products. A recent cross-sectional study found independent of obesity, the prevalence of MetS to be 30% among those whose diet was characterized by animal products as opposed to 19% in those with high consumption of vegetable fats [39]. Higher intakes of saturated fatty acids (SFA) have also been consistently associated with MetS components including decreased insulin sensitivity [36,40].…”
Section: Lipids and Metabolic Syndromementioning
confidence: 99%